Միգրացիոն գործընթացներն ու անվտանգային խնդիրները Հարավային Կովկասում - Գայանե Մելիքյան (ՀՀ ԳԱԱ հրատ.)
В этой статье понятие миграции определяется как проблема безопасности. Определяется миграционные процессы в регионе Южного Кавказа (Армения, НКР, Грузия, Азербайджан, Абхазия, Южная Осетия), выявлены основные проблемы в области безопасности. Опыт национальных исследований и методов работы имеет важное значение для изучения этой проблемы. Для изучения этой темы были использованы историко-сравнительный и социологические методы.In this article the conception of migration is defined, which is considered a safety problem. Migration processes are paid attention in the region of the South Caucasus (RA, NKR, Georgia, Azerbaijan, Abkhazia, South Osetia), discovering the main safety problems. The experiences of national research and work methods are of importance for the study of this subjects problem. Historical-comparative, socialogical methods were used for the study of this theme.
Keywords: Social Sciences; Sociology; Political Science